Rancang Bangun Aplikasi E-Commerce Berbasis Web Pada Toko Vapein - Sutrisno, Juan Pahlevy; Anwar, Nizirwan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2023)
In this era of rapid technological development, business people are required to keep up with the times so they can compete with other business people. With the existence of Covid-19, business people are required to utilize information technology because business activities are hampered by a ban on face-to-face meetings which has the potential to spread the virus. The researcher aims to create an e-commerce website for buying and selling vapes to increase vape sales that are affected by the Covid-19 virus. Researchers use the waterfall method in building this vape ecommerce website because it has the advantage of working on a structured project, stage by stage so as to minimize errors that may occur. From the results of data analysis carried out by researchers, it was found that standard system requirements, namely the existence of postage and automatic payments. The result of this research is that the VapeIn website can reach a wider range of customers and the data reports are better managed